2014
DOI: 10.1155/2014/685854
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Suppression of Interleukin-6 Gene Expression in Murine Macrophages by Nuclear Orphan Receptor REV-ERBα

Abstract: It is now evident that many nuclear hormone receptors can modulate target gene expression. REV-ERBα, one of the nuclear hormone receptors with the capacity to alter clock function, is critically involved in lipid metabolism, adipogenesis, and the inflammatory response. Recent studies suggest that REV-ERBα plays a key role in the mediation between clockwork and inflammation. The purpose of the current study was to investigate the role of REV-ERBα in the regulation of interleukin-6 (il6) gene expression in murin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
31
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 36 publications
6
31
1
Order By: Relevance
“…Statistical analysis of significance was calculated using one-way ANOVA followed by Tukey's post hoc test for multigroup comparisons or t test for two groups using the GraphPad Prism 6 software (GraphPad Software, Inc., San Diego, CA). regulating the inflammatory immune response (5,(17)(18)(19)(23)(24)(25). We have shown that CS reduces BMAL1 expression in mouse lungs through a SIRT1-dependent mechanism (3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical analysis of significance was calculated using one-way ANOVA followed by Tukey's post hoc test for multigroup comparisons or t test for two groups using the GraphPad Prism 6 software (GraphPad Software, Inc., San Diego, CA). regulating the inflammatory immune response (5,(17)(18)(19)(23)(24)(25). We have shown that CS reduces BMAL1 expression in mouse lungs through a SIRT1-dependent mechanism (3).…”
Section: Resultsmentioning
confidence: 99%
“…Abnormal regulation of circadian clocks in peripheral tissues is suggested to cause cell dysfunction and chronic diseases (8,30). It has been shown that the clock machinery including nuclear receptors controls inflammatory immune responses (5,17,19,(23)(24)(25)(31)(32)(33). We found that the level and expression of clock proteins (BMAL1 and PER2) and associated nuclear receptors (REV-ERBa) were reduced in PBMCs and sputum cells (mainly inflammatory cells [i.e., macrophages and neutrophils]) and in lungs from smokers and patients with COPD.…”
Section: Original Researchmentioning
confidence: 99%
“…Microglia rhythmically express circadian clock genes that can regulate function, including phagocytosis, inflammatory responses, and autophagy (Fonken et al, ; Ma, Li, Molusky, & Lin, ). This regulation may occur in part by mediating pro‐inflammatory chemokine expression (Lam et al, ; Sato et al, ). Microglia are highly sensitive to environmental cues and can immediately transform their morphology into distinctive phenotypes, including resting, classically activated (M1), and alternatively activated (M2) microglia (Ma, Wang, Wang, & Yang, ; Zhou et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Microglia rhythmically express circadian clock genes that can regulate function, including phagocytosis, inflammatory responses, and autophagy (Fonken et al, 2015;Ma, Li, Molusky, & Lin, 2012). This regulation may occur in part by mediating pro-inflammatory chemokine expression (Lam et al, 2013;Sato et al, 2014).…”
mentioning
confidence: 99%
“…REV-ERBs have been shown to regulate the expression of inflammatory cytokines interleukin-6 and Ccl2 [13,14]. REV-ERBs are widely expressed and it has been demonstrated that REVERBα is expressed in macrophages found in human atherosclerotic lesions [15].…”
Section: Introductionmentioning
confidence: 99%